(untitled) (Journal of Applied Business and Economics, 2020)
This paper reveals instant meaningful insights from endangered species international trade using descriptive analytics method using the Power BI analytical tool. The endangered species international trade 2016 dataset is analyzed by creating several Power BI visualizations which display revelations at a glance. Results display instant plots depicting the levels of exported and imported quantities of endangered wild fauna and flora with respect to several aspects such as their family, class, source, purpose and exporter/importer countries. This paper shows that use of Power BI visualizations can display faster analysis results and uncover relevant trade insights which can benefit the trade volume assessment and restriction monitoring process.